Pengaruh Alokasi Dana Desa (ADD) terhadap Tingkat Kemiskinan Masyarakat Desa Melalui Pertumbuhan Ekonomi Sebagai Variabel Intervening - Ica Maulidna Fatimah; Deviani Deviani (Universitas Negeri Padang, 2024)
This study aims to examine the effect of village fund allocation on poverty levels through economic growth. This research is an empirical study of districts/cities in the ten poorest provinces in Indonesia in 2021. This type of research is causal quantitative. The type of data used is secondary data. The secondary data used is data and information on village fund allocations, poverty rates and economic growth through the official BPS website and the village ministry. Methods of data analysis using Path Analysis (Path Analysis). The results of the research on the variable allocation of village funds with a probability value of 0.157 > 0.05, the allocation of village funds has a positive and insignificant effect on the poverty level of rural communities. The village fund allocation variable has a probability value of 0.375 > 0.05, so the village fund allocation has no positive and significant effect on economic growth. The economic growth variable with a probability value of 0.000 <0.05, means that economic growth has a negative and significant effect on the poverty level of rural communities. Hypothesis testing obtained a calculated t value = 1.1769 < t table 1.65 with a significance level of 0.05, so it can be concluded that the mediation coefficient is 0.030 and there is no intervening influence. The results obtained show that economic growth as an intervening variable has a positive and insignificant effect on the poverty level of rural communities.